Analisis Berita Hoax kepada Siswa terhadap Perilaku Bullying di Sekolah di SMP Nasrani 2 Medan - Agustin Pratama Sihotang; Deo Agung Haganta Barus; Eirene Dahlia Sidabutar; Nasywa Yasmin Purba; Abdinur Batubara (International Forum of Researchers and Lecturers, 2024)
This study aims to analyze the impact of hoax news on bullying behavior in SMP Nasrani 2 Medan. The proliferation of hoax news, facilitated by social media, has become a concerning issue affecting various aspects of society. Bullying, a prevalent problem among children and adolescents, manifests in various forms such as verbal, physical, and psychological abuse. Both phenomena have significant implications for individuals and communities, leading to distrust, conflict, and unhealthy societal values.Using a qualitative descriptive approach, this research delves into the dynamics between hoax news and bullying behavior among students at SMP Nasrani 2 Medan. Data collection involves literature review and observation of student characteristics, facilitated by interviews with students, class teachers, and school principals. The analysis interprets the relationship between misinformation and bullying behavior, aiming to identify patterns and insights to understand their impact comprehensively. The findings underscore the intertwined nature of hoax news and bullying behavior. Hoax news spreads rapidly through social media, exacerbating tensions and conflicts among students. Fear, hatred, and prejudice triggered by misinformation can fuel bullying behaviors, perpetuating a cycle of intimidation and harassment. The study reveals the importance of addressing both phenomena holistically to create a safe and inclusive school environment. Strategies to mitigate the impact of hoax news on bullying include education and awareness campaigns, strengthening school policies, fostering collaboration with parents, and implementing disciplinary measures. Teachers play a crucial role in educating students about critical thinking and empathy, recognizing signs of bullying, and mediating conflicts. By adopting a proactive and collaborative approach, schools can effectively address the challenges posed by hoax news and bullying, fostering a positive learning environment for all students.